Pain Experience and Behavior Management in Pediatric Dentistry: A Comparison between Traditional Local Anesthesia and the Wand Computerized Delivery System - Annelyse Garret-Bernardin; Tiziana Cantile; Vincenzo D’Antò; Alexandros Galanakis; Gabriel Fauxpoint; Gianmaria Fabrizio Ferrazzano; Sara De Rosa; Giulia Vallogini; Umberto Romeo; Angela Galeotti (Pain Research and Management)
Aim. To evaluate the pain experience and behavior during dental injection, using the Wand computerized delivery system versus conventional local anesthesia in children and adolescents. Methods. An observational crossover split mouth study was performed on 67 patients (aged 7 to 15 years), requiring local anesthesia for dental treatments in both sides of the dental arch. Patients received both types of injections in two separate appointments, one with the use of a Computer Delivery System (the Wand STA system) and one with the traditional syringe. The following data were recorded: pain rating; changes in heart rate; level of collaboration; patient satisfaction. The data were analyzed using ANOVA for quantitative outcomes and nonparametric analysis (Kruskal–Wallis) for qualitative parameters. Results. The use of the Wand system determined significantly lower pain ratings and lower increase of heart rate than the traditional syringe. During injection, the number of patients showing a relaxed behavior was higher with the Wand than with the traditional local anesthesia. The patient level of satisfaction was higher with the Wand compared to the conventional local anesthesia. Conclusions. The Wand system may provide a less painful injection when compared to the conventional local anesthesia and it seemed to be better tolerated with respect to a traditional syringe.